STRATEGY FOR DEVELOPING SOFT SKILLS IN GENERATION Z USING EDUCATIONAL TECHNOLOGY - Marzuki, Marzuki; Patemah, Patemah; Parta, Ida Bagus Made Wisnu (Jurnal Kajian Pendidikan dan Psikologi, 2024)
This study aims to explore the contribution of educational technology to developing soft skills among Generation Z students in public schools. We employed a qualitative research method, utilizing a case study approach. We collected data through observations and interviews with various stakeholders in public schools. The findings of the study indicate that educational technology positively contributes to enhancing students' soft skills. The use of educational technology facilitates interactive, creative, and adaptive learning, as well as collaboration and interaction among students from diverse backgrounds. However, to maximize the benefits of educational technology, we must address challenges like accessibility gaps and curriculum integration. The study concludes that educational technology holds great potential as a tool to prepare Generation Z for the demands and challenges of an increasingly complex and interconnected workforce.